Determination of critical section of wagon axle by considering dynamic and safety factors - Dikmen, Ferhat; Bayraktar, Meral; Guclu, Rahmi (ELSEVIER, 2019)
This paper aims to present how to determine the critical section of a railway axle that is broken due to fatigue. It has been achieved by examining failures in the axle of the train wagons. For this purpose, a full wagon model with 19 degree-of-freedom (DOF) has been considered to obtain the dynamic forces acting on the wagon axle. By examining the dynamic forces and moments that affect the axle the critical section of the axle is determined to predict the region of the broken region. Furthermore, the variation of the safety factor related to wagon load and wagon speed is discussed by considering the passengers. (C) 2019 The Authors. Published by Elsevier B.V. on behalf of Faculty of Engineering, Alexandria University.
Keywords: Rail vehicle axle; Safety factor; Dynamic analyses; Fracture; FATIGUE LIFE EVALUATION; RAILWAY; FAILURES; Engineering